2014
DOI: 10.1186/2045-3701-4-64
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in hydrogen peroxide imaging for biological applications

Abstract: Mounting evidence supports the role of hydrogen peroxide (H2O2) in physiological signaling as well as pathological conditions. However, the subtleties of peroxide-mediated signaling are not well understood, in part because the generation, degradation, and diffusion of H2O2 are highly volatile within different cellular compartments. Therefore, the direct measurement of H2O2 in living specimens is critically important. Fluorescent probes that can detect small changes in H2O2 levels within relevant cellular compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
85
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(85 citation statements)
references
References 101 publications
0
85
0
Order By: Relevance
“…Most published H2O2 probes, however, are not specific and show strong cross-sensitivities to other ROS or RNS [31]. One of the main employed mechanisms is the oxidative cleavage reaction [49] (Figure 2).…”
Section: Oxidative Cleavage-based Probesmentioning
confidence: 99%
See 1 more Smart Citation
“…Most published H2O2 probes, however, are not specific and show strong cross-sensitivities to other ROS or RNS [31]. One of the main employed mechanisms is the oxidative cleavage reaction [49] (Figure 2).…”
Section: Oxidative Cleavage-based Probesmentioning
confidence: 99%
“…Redox-sensitive GFP (roGFP) can be modified to produce a working H 2 O 2 sensor, by coupling it to yeast H 2 O 2 -sensing signaling peroxidase Orpl (roGFP-Orpl), which is not affected by pH changes in the physiological range [31].…”
Section: Genetically Encoded Probes-fluorescent Proteinsmentioning
confidence: 99%
“…19 Furthermore, numerous microbial studies have demonstrated the importance of H 2 O 2 in modulating bacterial ecology and signaling including antagonizing competitors in the oral biofilm. 1013 For example the commensal oral species Streptococcus gordonii (Sg) produces H 2 O 2 to control other pathobionts 13 thus supporting a healthy oral microbiome.…”
Section: Introductionmentioning
confidence: 99%
“…21 Recently, several specific and highly sensitive fluorescent probes have been developed for the detection of H 2 O 2 . [22][23][24] Some of these molecules have good performance in in vitro experiments. However, the limitation of conventional ROS fluorescent probes is their application in in vivo studies.…”
Section: Introductionmentioning
confidence: 99%